POLICY ENACTMENT IN NIGERIAN SECONDARY SCHOOLS: THE CASE OF THE NATIONAL POLICY ON EDUCATION - Ikpuri, Emmanuel Oghenerukevwe (South American Journal of Basic Education, Technical and Technological, 2019)
This research examined various factors affecting the (lack of) effectiveness in the enactment of the National Policy on Education (NPE) and assessed teachers’ perception on enactment of the National Policy on Education. A cross-sectional research design was employed, comprising an online survey of 100 teachers from 5 public school and 5 private schools in Nigeria. The online survey collected data on the background characteristics of the research participants, their experience, and perception regarding the enactment of the National Policy on Education. It also explored the factors influencing the enactment of the National Policy on Education, as well as the extent to which teachers are involved in the policy-making process. The research pointed out some factors that appear to impede the enactment of the NPE in practice. Some of the findings include; lack of clarity in NPE objectives, corruption, insufficient funding, inadequate facilities and infrastructures, poor government attitude towards education, lack of trained teachers, teachers lack knowledge regarding how to implement the NPE and head teachers’ lack of support for teachers with respect to NPE enactment in schools. Keywords: education; policy enactment; teachers; secondary schools; factors; Nigeria.